Taxonomic analysis of photovoltaic technology diffusion processes in European countries - Salamaga, Marcin (Publishing House of Wroclaw University of Economics and Business, 2025)
Aim: The aim of the article was to compare the processes of diffusion of innovations in photovoltaic technologies in European countries. Methodology: The study used the Bass model, and on the basis of individual estimates of the parameters of this model for each of the compared countries, their taxonomic analysis was carried out. Results: The innovators in the field of photovoltaic technologies turned out to be countries with high GDP and elevated expenditure on research and development, as well as countries whose favourable geographical location ensures a sufficiently large number of sunny days per year. This is followed, in turn, by countries with limited solar energy market potential located mainly in Central and Eastern Europe and some Scandinavian countries. Implications and recommendations: The results presented in the article may support decision-makers in creating an appropriate system for the synchronisation and coordination of policies and activities aimed at creating an electricity system with a high share of renewable energy sources. Comparative studies of the diffusion of solar technologies are also important from the point of view of assessing the effectiveness of actions aimed at creating zero-emission economies and possible adjustments to the European Green Deal. Originality/value: The article presents an original comparative analysis of the diffusion profiles of innovations in photovoltaics in European countries, thus the research results fill the research gap in this area. Keywords: renewable energy sources, photovoltaics, Bass model, learning curves, Ward’s method
Argumenta Oeconomica, 2025, Nr 2 (55), s. 21-33
Keywords: renewable energy sources; photovoltaic; bass model; learning curves; Ward's method